Polyurethane adhesive having a low free monomeric isocyanate content
Patent Information
- Application Number
- CN202580020941.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-11
- Filing Date
- 2025-03-10
- Publication Date
- 2026-10-27
AI Technical Summary
在提供依赖于异氰酸酯封端的聚合物的双组分聚氨酯粘合剂时的另一个特别挑战是实现最终的高粘接强度,特别是与足够长适用期的组合
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to two-component polyurethane adhesives and related kits and methods. In particular, this invention relates to polyurethane adhesives with low free monomer isocyanate content that still exhibit high performance in demanding applications. These polyurethane adhesives are particularly suitable for applications where rapid formation and delayed establishment of high bond strength are both possible, such as window assembly. Background Technology
[0002] It is well known that high-performance polyurethane adhesives typically used in industrial applications can be formed from two-component systems, which are often referred to as "component A" and "component B," and when mixed, they polymerize into polyurethane.
[0003] Component "A" contains diisocyanate or polyisocyanate and optional other additives, while component "B" typically contains polyol, catalyst, and optional other additives. These two components are packaged and stored in separate containers or in different compartments within the same container. Typically, components "A" and "B" are delivered via separate lines to a dispensing device (such as an impact-mixing or static-mixing spray gun or pouring gun), usually at a volume ratio of approximately 10:1 to 1:10. In systems with two separate containers, the two components remain separate throughout the system until they converge in the mixing section of the dispensing device (such as a mixing nozzle or mixing chamber). During dispensing, the liquid contents are discharged as a mixture that reacts and cures to form a polyurethane adhesive. The polyurethane industry traditionally considers the isocyanate component as component "A" and the polyol component as component "B." However, in some regions, the designation of "A" and "B" may be reversed.
[0004] One example of an industry that relies on the use of high-performance two-component polyurethane adhesives is window assembly. Aluminum-framed windows are made by assembling multiple straight aluminum profiles into a window frame, typically using aluminum anchors to connect two profiles. After assembly, adhesives are used to bond these components together. Adhesives used for such applications are typically two-component polyurethane adhesives due to their high performance.
[0005] Despite the advantageous properties of polyurethane adhesives, they also have some drawbacks. One of the most serious drawbacks is the high content of monomeric isocyanates (especially highly volatile diisocyanates) present in the "A" component used to prepare these adhesives. These compounds are considered harmful to the environment and health. The high content of monomeric isocyanates in many known polyurethane adhesives raises concerns about worker safety when applying two-component adhesives.
[0006] Therefore, there is great interest in developing novel two-component polyurethane adhesives that can significantly reduce these hazards. One way to reduce the free monomeric isocyanate (FMI) content of the isocyanate component in two-component polyurethane adhesives is to partially or completely replace the monomeric isocyanate with polymeric isocyanates having isocyanate end groups (i.e., isocyanate-terminated polymers). These isocyanate-terminated polymers still exhibit a degree of reactivity due to the presence of unreacted isocyanate end groups and exhibit little to no volatility, thus addressing the aforementioned health concerns.
[0007] However, polyurethane adhesives that rely on isocyanate-terminated polymers have several drawbacks. Typically, these products perform worse than known monomer-based isocyanate-based products because properties such as viscosity, pot life, curing time, usable temperature range, post-cured hardness, and post-cured tensile strength are adversely affected, and they often fail to meet the industry's requirements for viable alternatives to known monomer-based isocyanate-based products.
[0008] The inventors have discovered that a significant challenge in providing two-component polyurethane adhesives for isocyanate-terminated polymers is achieving a combination of sufficiently delayed curing (resulting in a long pot life) and sufficiently short time exhibiting strong adhesion (the strong bond where objects are bonded together using the adhesive). Pot life is the amount of time a mixture of two components remains usable from the start of mixing until it reaches excessively high viscosity. A sufficiently long pot life (e.g., at least 30 minutes) is desirable to prevent clogging of the static mixer or other parts of the dispensing system used to dispense the two-component polyurethane foam between applications. On the other hand, once delayed curing begins, high bond strength should be reached quickly enough within a short timeframe, such as a few hours (e.g., two or five hours). Slow strength buildup is problematic, especially at lower temperatures (common in industrial environments during winter). Another particular challenge in providing two-component polyurethane adhesives for isocyanate-terminated polymers is achieving the ultimate high bond strength, particularly in combination with a sufficiently long pot life.
[0009] One object of the present invention is to provide improved two-component polyurethane adhesives and kits for their formation, particularly having a low free monomer isocyanate content.
[0010] One object of the present invention is a two-component polyurethane adhesive with low free monomer isocyanate content and kits for forming therewith, which have low initial viscosity, extended pot life and / or shortened time required to reach predetermined bond strength.
[0011] One object of the present invention is a two-component polyurethane adhesive with low free monomer isocyanate content and a kit for forming therewith, the adhesive having high final bond strength.
[0012] One object of the present invention is a two-component polyurethane adhesive with low free monomer isocyanate content and a kit for forming therewith, the adhesive having a wide usable temperature range. Summary of the Invention
[0013] The inventors have discovered that one or more of these objectives can be achieved by employing a kit for forming a two-component polyurethane adhesive according to the invention, the kit using an isocyanate component with a low FMI content along with a tin catalyst containing sulfur atoms. As shown in the appended examples, such a combination has been found to allow for adhesives that offer both greater ease of handling and optimized performance (such as pot life, curing time, usable temperature range, Shore (hardness) hardness, and tensile strength). In particular, the invention achieves a unique combination of long pot life and rapid strength gains (which are particularly significant at lower temperatures). Surprisingly, as shown in the appended examples, other conventional classes of metal catalysts have been found to fail to produce the desired combination of performance.
[0014] In a first aspect, the present invention relates to a two-component polyurethane adhesive-forming kit, wherein the kit comprises an isocyanate component and a polyol component, wherein the isocyanate component comprises an isocyanate-terminated polymer, wherein the free monomeric isocyanate (FMI) content of the isocyanate component is equal to or less than 1000 ppm, wherein the polyol component comprises a polyol, wherein the polyol component and / or the isocyanate component comprises a polyol and a tin catalyst, wherein the tin catalyst comprises sulfur atoms.
[0015] In another aspect, the present invention relates to a kit for forming a two-component polyurethane adhesive, wherein the kit comprises an isocyanate component and a polyol component, wherein the isocyanate component comprises an isocyanate-terminated polymer, wherein the free monomeric isocyanate (FMI) content of the isocyanate component is equal to or less than 1000 ppm, wherein the polyol component comprises a polyol, wherein the polyol component and / or the isocyanate component comprises a metal catalyst, wherein µ 30 µ0 is less than 3:1, preferably less than 2:1, and where µ 90The viscosity of the mixture of polyol and isocyanate components is greater than 10:1, preferably greater than 15:1, where µ0 is the viscosity measured immediately after mixing, and the mixture is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5. 30 The viscosity is the same mixture measured 30 minutes after mixing, and the µ viscosity is... 90 The viscosity is the same mixture measured 90 minutes after mixing, and these viscosities are determined according to the viscosity protocol.
[0016] In another aspect, the present invention relates to a kit for forming a two-component polyurethane adhesive, wherein the kit comprises an isocyanate component and a polyol component, wherein the isocyanate component comprises an isocyanate-terminated polymer, wherein the free monomeric isocyanate (FMI) content of the isocyanate component is equal to or less than 1000 ppm, wherein the polyol component comprises a polyol, wherein the polyol component and / or the isocyanate component comprises a metal catalyst, wherein t 2000 Greater than 45 minutes, preferably greater than 50 minutes, more preferably greater than 60 minutes, where t 2000 The time required for the viscosity of the mixture of the polyol component and the isocyanate component to reach 2000 Pa·s (measured immediately after the two components are mixed), wherein the mixture of the polyol component and the isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5, and wherein the viscosity is measured according to a viscosity measurement procedure.
[0017] The preferred option is:
[0018] • The viscosity of the polyol component is in the range of 0.3 – 2000 Pa·s, wherein the viscosity is determined according to the viscosity measurement procedure, preferably in the range of 0.8-1200 Pa·s;
[0019] • The viscosity of the isocyanate component is in the range of 0.3 - 2000 Pa·s, wherein the viscosity is determined according to a viscosity measurement procedure, preferably in the range of 0.8 - 1200 Pa·s; and / or
[0020] • The viscosity of the mixture of polyol component and isocyanate component, measured immediately after mixing, is in the range of 0.3-2000 Pa·s, wherein the viscosity is determined according to a viscosity measurement procedure, preferably in the range of 0.8-1200 Pa·s, and wherein the mixture of polyol component and isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5.
[0021] The tin catalyst is preferably selected from the group consisting of tin mercaptides, tin thioglycolates and combinations thereof, and more preferably from the group consisting of dialkyltin mercaptides, dialkyltin thioglycolates and combinations thereof.
[0022] Preferably, the lap shear strength of the mixture of polyol component and isocyanate component, measured after curing at 5°C for 24 hours, is greater than 1 N / mm. 2 Preferably, the strength is higher than 1.3 N / mm 2 More preferably, higher than 1.5 N / mm 2 The optimal value is higher than 2 N / mm 2 The lap shear strength was measured according to the lap shear strength determination procedure described herein.
[0023] Preferably, t 2000 Greater than 45 minutes, preferably greater than 50 minutes, more preferably greater than 60 minutes, where t 2000 It is the time required for the viscosity of the mixture of polyol component and isocyanate component to reach 2000 Pa·s (measured immediately after the two components are mixed), wherein the mixture of polyol component and isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5, and wherein the viscosity is measured according to a viscosity measurement procedure.
[0024] In another aspect, the present invention provides a polyurethane adhesive that is obtained by mixing a polyol component and an isocyanate component of a kit as described herein, preferably by mixing the components at a stoichiometric ratio of NCO / OH in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5.
[0025] In another aspect, the present invention provides the use of the kits or adhesives described herein for joining two or more objects. The joined objects may be of the same material or different materials. In some embodiments, the materials of the objects are selected from metals, plastics (including fiber-reinforced plastics and foamed polymers), wood, bitumen, glass, fiberglass, mineral wool, bituminous roofing, plaster, and concrete. In some embodiments, the use is for joining a first object, which is an insulation material (preferably a foamed polymer, such as expanded polystyrene), to a second object selected from wood, metal, or polyvinyl chloride. Such applications can be seen, for example, in the production of so-called sandwich insulation panels. A preferred use is for joining an aluminum object to another object, most preferably for joining two or more aluminum objects.
[0026] In another aspect, the present invention provides a method for forming a polyurethane adhesive, comprising:
[0027] • Provide isocyanate components as described herein;
[0028] • Provide polyol components as described herein; and
[0029] • The isocyanate component and the polyol component are mixed, preferably at an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, more preferably 0.9 to 3.0, and more preferably 1.0 to 2.5.
[0030] In another aspect, the present invention provides the use of tin catalysts containing sulfur atoms, as described herein, for delaying the curing of mixtures of polyols and isocyanate components as described herein. The polyol is preferably a polyol as described herein, and is preferably provided in the form of a polyol component as described herein. Detailed Implementation
[0031] As used herein, the terms “including” and its variations such as “comprising” and “containing” should be interpreted in an open-ended and inclusive manner, meaning that the described implementation scheme includes the listed features, but does not exclude the presence of other features, provided that such other features do not render the implementation scheme unworkable.
[0032] As used herein, expressions such as "an embodiment," "a particular embodiment," or "implementation" should be interpreted as meaning that a particular feature, structure, or characteristic described with respect to that embodiment is included in at least one embodiment. Therefore, such expressions appearing in different places throughout the specification do not necessarily refer to the same embodiment. Furthermore, these particular features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. For example, certain features of the disclosure described herein in the context of various embodiments are also explicitly contemplated for combination in a single embodiment.
[0033] Unless otherwise expressly provided, the singular forms “a,” “an,” and “the” used herein shall be interpreted to include plural references. It should also be noted that, unless otherwise expressly provided, the term “or” is generally used in its broadest sense, meaning “and / or.”
[0034] Throughout this document, whenever a compound is referred to as a salt, unless otherwise expressly defined, this should be understood to include the anhydrous form of the compound as well as any solvates (especially hydrates).
[0035] In the context of this invention, the NCO / OH stoichiometric ratio is the molar ratio of the total amount of unreacted NCO groups from any source in the isocyanate component to the total amount of unreacted OH groups from any source in the polyol component before the polyol component comes into contact with the isocyanate component.
[0036] As used herein, “free monomeric isocyanate (FMI) content” refers to the amount of unreacted isocyanate monomers present in the isocyanate component. This amount is expressed in ppm (w / w) and is based on the total isocyanate component. For the purposes of this invention, the free monomeric isocyanate (FMI) content is determined using liquid chromatography-mass spectrometry (LC-MS).
[0037] As used herein, NCO content (e.g., in the context of NCO content in isocyanate-terminated polymers) refers to the amount of unreacted NCO groups (in weight %). NCO content is typically an average NCO content, which can be conveniently calculated or determined by titration, such as according to DIN ISO 14896 (2009).
[0038] When the preparation of a mixture of polyol and isocyanate components is mentioned herein, the mixture is preferably prepared using a dual asymmetric centrifugal mixer (such as the Haushchild® SpeedMixer) at 2500 rpm for 30 seconds.
[0039] The viscosity mentioned in this article refers to complex viscosity and is determined using the method described elsewhere in this article as a “Viscosity Measurement Procedure”.
[0040] In various instances of this disclosure, the properties of mixtures obtained by mixing a polyol component with an isocyanate component at an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5 are mentioned. In any of these embodiments, an NCO / OH stoichiometric ratio of about 1.1 is preferred.
[0041] Two-component kit
[0042] In a first aspect, the present invention relates to a kit for forming a two-component polyurethane adhesive, wherein the kit comprises an isocyanate component and a polyol component, wherein the isocyanate component comprises an isocyanate-terminated polymer, wherein the free monomeric isocyanate (FMI) content of the isocyanate component is equal to or less than 1000 ppm, wherein the polyol component comprises a polyol, wherein the polyol component and / or the isocyanate component comprises a tin catalyst, wherein the tin catalyst comprises sulfur atoms.
[0043] In another aspect, the present invention relates to a kit for forming a two-component polyurethane adhesive, wherein the kit comprises an isocyanate component and a polyol component, wherein the isocyanate component comprises an isocyanate-terminated polymer, wherein the free monomeric isocyanate (FMI) content of the isocyanate component is equal to or less than 1000 ppm, wherein the polyol component comprises a polyol, wherein the polyol component and / or the isocyanate component comprises a metal catalyst, wherein µ 30 µ0 is less than 3:1, preferably less than 2:1, and where µ 90 The viscosity of the mixture of polyol and isocyanate components is greater than 10:1, preferably greater than 15:1, where µ0 is the viscosity measured immediately after mixing, and the mixture is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5. 30 The viscosity is the same mixture measured 30 minutes after mixing, and the µ viscosity is... 90 It is the viscosity of the same mixture measured 90 minutes after mixing, and the viscosity is determined according to the viscosity measurement procedure.
[0044] In another aspect, the present invention relates to a kit for forming a two-component polyurethane adhesive, wherein the kit comprises an isocyanate component and a polyol component, wherein the isocyanate component comprises an isocyanate-terminated polymer, and the free monomeric isocyanate (FMI) content of the isocyanate component is equal to or less than 1000 ppm, wherein the polyol component comprises a polyol, and wherein the polyol component and / or the isocyanate component comprises a metal catalyst, wherein t 2000 Greater than 45 minutes, preferably greater than 50 minutes, more preferably greater than 60 minutes, where t 2000 It is the time required for the viscosity of the mixture of polyol component and isocyanate component to reach 2000 Pa·s (measured immediately after the two components are mixed), wherein the mixture of polyol component and isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5, and wherein the viscosity is measured according to a viscosity measurement procedure.
[0045] Any reference to the "kit" of the invention in this specification should be interpreted as referring to any of these aspects of the invention, preferably the first aspect. Similarly, any reference to "isocyanate component," "polyol component," or any part thereof in this specification should be interpreted as referring to any of these aspects of the invention, preferably the first aspect. Similarly, any reference to the "adhesive" of the invention in this specification should be interpreted as referring to an adhesive available through any of these aspects of the invention, preferably an adhesive available through the first aspect.
[0046] The polyurethane adhesive of the present invention is not a foamed product like polyurethane insulation foam. Therefore, the kit is preferably used to form a substantially non-foamed polyurethane adhesive. In other words, the polyurethane adhesive of the present invention is highly preferably free of a honeycomb structure. Therefore, the kit is preferably used to form a polyurethane adhesive without a honeycomb structure. Preferably, the isocyanate component and the polyol component each contain less than 2% by weight (based on the total weight of the respective components) of a blowing agent, preferably less than 1% by weight, and most preferably about 0% by weight. The blowing agent can be selected from chemical blowing agents or physical blowing agents (the latter are also known as propellants). In some embodiments, the isocyanate component and the polyol component each contain less than 2% by weight (based on the total weight of the respective components) of a blowing agent selected from: C1–C4 saturated or unsaturated hydrocarbons (e.g., n-pentane, n-butane, isobutane, n-hexane, 2-methylbutane, propane, 1-pentene, butene, 2-methyl-2-butene, cyclobutane, cyclopentane, cyclohexane), vinyl chloride, chloromethane, chlorofluorocarbons, hydrochlorofluorocarbons, hydrohalogenated alkenes, air, carbon dioxide, argon, nitrogen, nitrous oxide, dimethyl ether, diethyl ether, dimethoxymethane, methyl formate, water, and combinations thereof.
[0047] The isocyanate and polyol components of the kits of the present invention are different compositions and are stored separately from each other before being mixed to form the polyurethane adhesive of the present invention. The kits may be presented in separate containers (e.g., an isocyanate container containing the isocyanate component and a polyol container containing the polyol component). The two components may also be presented in a single container, wherein the two components are contained in different internal compartments.
[0048] The kit may include a dispensing device, such as a caulking gun, for dispensing the two components. The dispensing device is preferably equipped with a mixer, such as an impact mixer or a static mixer.
[0049] The kit for forming a two-component polyurethane adhesive according to the present invention preferably includes an isocyanate component and a polyol component in amounts corresponding to the stoichiometric ratios typically used for adhesive formation. Therefore, in a preferred embodiment, a kit for forming a two-component polyurethane adhesive according to the present invention is provided, wherein the NCO / OH stoichiometric ratio determined for all components of the kit is in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5.
[0050] Isocyanate components
[0051] According to the present invention, the isocyanate component comprises an isocyanate-terminated polymer, and its free monomeric isocyanate (FMI) content is equal to or less than 1000 ppm. The inventors have discovered that, using the compositions of the present invention, even lower free monomeric isocyanate contents can be prepared while still achieving a rapid increase in strength. Therefore, in a preferred embodiment of the present invention, the isocyanate component comprises an isocyanate-terminated polymer, and its free monomeric isocyanate (FMI) content is equal to or less than 750 ppm, preferably less than 500 ppm.
[0052] Isocyanate-terminated polymers typically contain two or more unreacted isocyanate groups, which can be achieved by preparing the polymer in the presence of an excess of isocyanate monomer. If the polymer is linear, it preferably contains two unreacted isocyanate groups, while if the polymer is branched, it may contain more than two unreacted isocyanate groups. The amount of unreacted isocyanate groups is typically expressed as NCO content, which is an average of the weight % of NCO groups in the polymer (as explained above). In all embodiments of the invention, the NCO content of the isocyanate-terminated polymer is preferably at least 4% by weight, more preferably at least 7% by weight. The NCO content is typically less than 40% by weight, for example, less than 35% by weight.
[0053] Isocyanate-terminated polymers can be obtained by polymerizing one or more isocyanate monomers, optionally together with one or more other monomers containing two or more isocyanate reactive functional groups. The one or more other monomers may comprise polyols and / or monomers other than alcohols containing two or more isocyanate reactive functional groups. The isocyanate monomer is preferably selected from the group consisting of: aromatic diisocyanates (such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, mixtures of 2,4-toluene diisocyanate and 2,6-toluene diisocyanate, crude toluene diisocyanate, methylene diphenyl diisocyanate, etc.); aromatic triisocyanates (such as 4,4',4”-triphenylmethane triisocyanate, 2,4,6-toluene triisocyanate); aromatic tetraisocyanates (such as 4,4'-dimethyldiphenylmethane-2,2',5,5'-tetraisocyanate); aralkyl polyisocyanates (such as xylene diisocyanate); aliphatic polyisocyanates (such as hexamethylene-1,6-diisocyanate, lysine diisocyanate methyl ester); polymethylene polyphenyl isocyanates; hydrogenated methylene diphenyl isocyanates; Isoisocyanates; isophenyl diisocyanates; naphthalene-1,5-diisocyanates; 1-methoxyphenyl-2,4-diisocyanates; 4,4'-biphenyl diisocyanates; 3,3'-dimethoxy-4,4'-biphenyl diisocyanates; 3,3'-dimethyl-4,4'-biphenyl diisocyanates; 3,3'-dimethyldiphenylmethane-4,4'-diisocyanates; alkylene diisocyanates (such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-methylenebis(cyclohexyl)isocyanate); aromatic polyisocyanates (such as isophenyl diisocyanate and terephthalene diisocyanate, polymethylene polyphenyl isocyanate, 2,4-toluene diisocyanate and 2,6-toluene diisocyanate, dianisidine diisocyanate). diisocyanate, bitoylene isocyanate, naphthalene-1,4-diisocyanate, bis(4-isocyanatophenyl), methene, bis(2-methyl-4-isocyanatophenyl)methane; and combinations thereof. In a preferred embodiment of the invention, the isocyanate-terminated polymer can be obtained by polymerizing one or more isocyanate monomers, optionally together with one or more other monomers comprising two or more isocyanate reactive functional groups; wherein the one or more isocyanate monomers are selected from alkylene diisocyanates and aromatic polyisocyanates, preferably wherein the one or more isocyanate monomers are selected from hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI) and / or methylene diisocyanate (MDI).
[0054] The isocyanate-terminated polymer preferably has:
[0055] • Viscosity in the range of 0.3 – 2000 Pa·s, wherein the viscosity is determined according to a viscosity measurement procedure, preferably in the range of 0.5 – 1400 Pa·s; and / or
[0056] • Number-average molecular weight in the range of 250–10,000 g / mol, preferably 500–5000, wherein the number-average molecular weight is determined according to the procedure for determining number-average molecular weight.
[0057] The preferred isocyanate-terminated polymers are:
[0058] • An isocyanate-polyol prepolymer can be obtained by polymerizing a first isocyanate monomer with a polyol, preferably a polyol selected from the group consisting of polyether polyols, polyester polyols, or mixtures thereof; or
[0059] • Isocyanate polymers can be obtained by polymerizing a second isocyanate monomer without the presence of polyols.
[0060] To make the isocyanate-polyol prepolymer isocyanate-terminated, an excess of isocyanate monomer is required. Therefore, the isocyanate-polyol prepolymer is preferably obtained by polymerizing a first isocyanate monomer with a polyol, preferably with a polyol as described herein in the context of polyol composition, wherein an excess of NCO groups relative to the OH groups is used. A suitable NCO:OH ratio for polymerization is in the range of 0.8-1.25. In a preferred embodiment of the invention, the NCO content of the isocyanate-polyol prepolymer is at least 5% by weight (based on the total weight of the isocyanate-polyol prepolymer), preferably at least 8% by weight, and most preferably in the range of 8-10% by weight. The first isocyanate monomer preferably comprises or consists of hexamethylene diisocyanate (HDI).
[0061] The isocyanate polymer can preferably be obtained by polymerizing only the isocyanate monomer. Alternatively, the isocyanate polymer can be obtained by having an isocyanate monomer and other monomers (such as bifunctional amines) that are alcohol-free and contain two or more isocyanate reactive functional groups other than alcohols. In this case, NCO groups are used in stoichiometric excess relative to the other functional groups during polymerization. A suitable ratio of NCO groups to the other functional groups used for polymerization is in the range of 0.9-1.3. In a preferred embodiment of the invention, the isocyanate polymer has an NCO content of at least 13% by weight (based on the total weight of the isocyanate-polyol prepolymer), preferably at least 16% by weight, and most preferably at least 20% by weight. The second isocyanate monomer preferably comprises toluene diisocyanate (TDI) and / or methylene diisocyanate (MDI) or consists of toluene diisocyanate (TDI) and / or methylene diisocyanate (MDI).
[0062] In embodiments of the invention, based on the total weight of the isocyanate component, the isocyanate component contains more than 40% by weight of isocyanate-terminated polymer, preferably more than 45% by weight, more preferably more than 50% by weight, and most preferably more than 55% by weight. In embodiments of the invention, based on the total weight of the isocyanate component, the isocyanate component contains less than 80% by weight of isocyanate-terminated polymer, preferably less than 75% by weight, more preferably less than 70% by weight, and most preferably less than 65% by weight. In a preferred embodiment, based on the total weight of the isocyanate component, the isocyanate component contains isocyanate-terminated polymer in the range of 40% to 80% by weight, preferably in the range of 45% to 75% by weight, more preferably in the range of 50% to 70% by weight, and most preferably in the range of 55% to 65% by weight. The total amount of isocyanate in the isocyanate component is also preferably in the range of 45% to 75% by weight, more preferably in the range of 50% to 70% by weight, and most preferably in the range of 55% to 65% by weight. In a highly preferred embodiment, the only isocyanate contained in the isocyanate component is an isocyanate-terminated polymer according to any embodiment described herein, and less than 1000 ppm of free monomeric isocyanate.
[0063] The isocyanate component according to the invention may optionally contain one or more other additives. The total amount of all components in the isocyanate component is 100% by weight, based on the total weight of the polyol component. In embodiments of the invention, the isocyanate component contains one or more other additives selected from: fillers, flame retardants, colorants, rheology modifiers, desiccant (moisture scavenger), and / or catalysts.
[0064] The isocyanate component according to the invention is preferably substantially anhydrous. In a preferred embodiment, it contains less than 0.1% by weight of water.
[0065] According to a preferred embodiment of the invention, the isocyanate component comprises a filler, preferably selected from mineral fillers, metal oxide fillers, fly ash, bottom ash, carbon black, glass, and combinations thereof. Such fillers can also act as rheology modifiers and / or dehumidifiers. Examples include aluminum silicate, aluminum hydroxide, fumed silica, calcium silicate, magnesium silicate, dolomite, calcium carbonate, barium sulfate, calcium sulfate, glass fiber, hollow glass microspheres, carbon black, chalk, titanium dioxide, zinc oxide, siloxanes, and / or silica. The filler may be surface-modified, and any reference to fillers in this disclosure should be interpreted as referring to fillers optionally surface-modified. Surface modification of fillers is well known to those skilled in the art. Preferred surface modification includes surface treatment with fatty acids (e.g., stearic acid) or silanes (e.g., alkoxysilanes). Preferred fillers for the isocyanate component are fillers comprising silica, calcium carbonate, and / or aluminum silicate, or fillers primarily composed of silica, calcium carbonate, and / or aluminum silicate.
[0066] In embodiments of the invention, the isocyanate component contains filler in an amount greater than 10% by weight, preferably greater than 25% by weight, more preferably greater than 32% by weight, and more preferably greater than 35% by weight (based on the total weight of the isocyanate component). In embodiments of the invention, the isocyanate component contains filler in an amount less than 65% by weight, preferably less than 55% by weight, and more preferably less than 45% by weight (based on the total weight of the isocyanate component). In a preferred embodiment of the invention, the isocyanate component contains filler in an amount of 10-65% by weight, more preferably 25-55% by weight, and even more preferably 32-45% by weight. In a highly preferred embodiment of the invention, the isocyanate component contains filler (comprising silica, calcium carbonate, and / or aluminum silicate) in an amount of 10-65% by weight, more preferably 25-55% by weight, and even more preferably 32-45% by weight (based on the total weight of the isocyanate component).
[0067] In a preferred embodiment of the invention, the isocyanate component includes a filler, such as porous aluminosilicate, which also acts as a desiccant. The desiccant is preferably included in the isocyanate component in an amount of 0.5-10% by weight, more preferably 1-8% by weight, more preferably 1.5-7% by weight, and even more preferably 2-6% by weight (based on the total weight of the isocyanate component).
[0068] In a preferred embodiment of the invention, the isocyanate component includes a filler, such as fumed silica, which also acts as a rheology modifier. The rheology modifier is preferably included in the isocyanate component in an amount of 0.1-10% by weight, preferably 0.5-8% by weight, more preferably 0.5-4% by weight, and even more preferably 1-3% by weight (based on the total weight of the isocyanate component).
[0069] Preferably, the total combined amount of isocyanate-polymer and filler (preferably mineral filler) contained in the isocyanate component is in the range of 85-100% by weight (based on the total weight of the isocyanate component), more preferably in the range of 95-100% by weight, and most preferably in the range of 98-100% by weight.
[0070] The isocyanate component according to the invention may optionally contain one or more catalysts other than tin catalysts containing sulfur atoms, which may be present and discussed elsewhere herein. Other catalysts present in the isocyanate component may be any catalyst known in the art and suitable for catalyzing the reaction between the polyol component and the isocyanate component. Examples of suitable catalysts include metal catalysts, amine catalysts, and morpholine catalysts. In some embodiments of the invention, the isocyanate component contains other metal catalysts, wherein the metal is selected from Sn, Bi, Zn, Ti, Zr, or Al.
[0071] In embodiments of the present invention, the total amount of catalyst present in the isocyanate component is greater than 0.01% by weight (based on the total weight of the isocyanate component), preferably greater than 0.05% by weight, more preferably greater than 0.1% by weight, more preferably greater than 0.2% by weight, and more preferably greater than 0.3% by weight. In embodiments of the present invention, the total amount of catalyst present in the isocyanate component is 0.01-10% by weight (based on the total weight of the isocyanate component), preferably 0.05-7.5% by weight, and more preferably 0.1-5% by weight. In several embodiments, the total amount of catalyst present in the isocyanate component is 0.01-10 wt%, 0.01-9.5 wt%, 0.01-9 wt%, 0.01-8.5 wt%, 0.01-8 wt%, 0.01-7.5 wt%, 0.01-7 wt%, 0.01-6.5 wt%, 0.01-6 wt%, 0.01-5.5 wt%, 0.01-5 wt%, 0.01-4.5 wt%, 0.01-4 wt%, 0.01-3.5 wt%, 0.01-3 wt%, 0.01-2.5 wt%, 0.01-2 wt%, 0.01-1.5 wt%, and 0.01-1 wt% (based on the total weight of the isocyanate component). In several embodiments, the total amount of catalyst present in the isocyanate component is 0.05-10 wt%, 0.05-9.5 wt%, 0.05-9 wt%, 0.05-8.5 wt%, 0.05-8 wt%, 0.05-7.5 wt%, 0.05-7 wt%, 0.05-6.5 wt%, 0.05-6 wt%, 0.05-5.5 wt%, 0.05-5 wt%, 0.05-4.5 wt%, 0.05-4 wt%, 0.05-3.5 wt%, 0.05-3 wt%, 0.05-2.5 wt%, 0.05-2 wt%, 0.05-1.5 wt%, and 0.05-1 wt% (based on the total weight of the isocyanate component). In several embodiments, the total amount of catalyst present in the isocyanate component is 0.1-10 wt%, 0.1-9.5 wt%, 0.1-9 wt%, 0.1-8.5 wt%, 0.1-8 wt%, 0.1-7.5 wt%, 0.1-7 wt%, 0.1-6.5 wt%, 0.1-6 wt%, 0.1-5.5 wt%, 0.1-5 wt%, 0.1-4.5 wt%, 0.1-4 wt%, 0.1-3.5 wt%, 0.1-3 wt%, 0.1-2.5 wt%, 0.1-2 wt%, 0.1-1.5 wt%, and 0.1-1 wt% (based on the total weight of the isocyanate component).In several embodiments, the total amount of catalyst present in the isocyanate component is 0.2-10 wt%, 0.2-9.5 wt%, 0.2-9 wt%, 0.2-8.5 wt%, 0.2-8 wt%, 0.2-7.5 wt%, 0.2-7 wt%, 0.2-6.5 wt%, 0.2-6 wt%, 0.2-5.5 wt%, 0.2-5 wt%, 0.2-4.5 wt%, 0.2-4 wt%, 0.2-3.5 wt%, 0.2-3 wt%, 0.2-2.5 wt%, 0.2-2 wt%, 0.2-1.5 wt%, and 0.2-1 wt% (based on the total weight of the isocyanate component). In several embodiments, the total amount of catalyst present in the isocyanate component is 0.3-10 wt%, 0.3-9.5 wt%, 0.3-9 wt%, 0.3-8.5 wt%, 0.3-8 wt%, 0.3-7.5 wt%, 0.3-7 wt%, 0.3-6.5 wt%, 0.3-6 wt%, 0.3-5.5 wt%, 0.3-5 wt%, 0.3-4.5 wt%, 0.3-4 wt%, 0.3-3.5 wt%, 0.3-3 wt%, 0.3-2.5 wt%, 0.3-2 wt%, 0.3-1.5 wt%, and 0.3-1 wt% (based on the total weight of the isocyanate component).
[0072] In a preferred embodiment of the invention, the viscosity of the isocyanate component is in the range of 0.3 – 2000 Pa·s, wherein the viscosity is determined according to a viscosity measurement procedure, preferably in the range of 0.5 – 1400 Pa·s.
[0073] polyol components
[0074] The polyol component may contain a single polyol or multiple polyols, which are typically used and sold as polyol premixes. The one or more polyols present in the polyol component may be any polyol known in the art for the preparation of polyurethane adhesives.
[0075] As used herein, “polyol” refers to a molecule having more than 1.0 hydroxyl groups per molecule on average. The total mixture of polyols present in the polyol component may be added separately to the polyol component or may be added as a pre-blended polyol mixture (which may be sold in this manner).
[0076] Available polyols include one or more of the following: sucrose-containing polyols; phenol- or phenolic resin-containing polyols; glucose-containing polyols; sorbitol-containing polyols; methyl glucoside-containing polyols; aromatic polyester polyols; aliphatic polyester polyols; aromatic polyether polyols; aliphatic polyether polyols; polybutadiene polyols; polycaprolactone polyols; polycarbonate polyols; hydroxyl-terminated polyolefin polyols; grafted polyols; glycerol; ethylene glycol; diethylene glycol; propylene glycol-containing polyols; graft copolymers of polyether polyols with vinyl polymers; copolymers of polyether polyols with polyurea; products condensed from one or more of the following (a) and one or more of the following (b): (a) glycerol, ethylene glycol, diethylene glycol, trimethylolpropane, pentaerythritol, soybean oil, lecithin, tall oil, palm oil, castor oil; (b) ethylene oxide, propylene oxide, mixtures of ethylene oxide and propylene oxide; or combinations thereof.
[0077] The preferred polyols are selected from the group consisting of polyether polyols, polyester polyols, and combinations thereof.
[0078] Examples of polyether polyols include alkylene oxide adducts of active hydrogen compounds (such as water, alcohols, phenols, etc.). Preferred alkylene oxides are styrene oxide, ethylene oxide, propylene oxide, and / or butane oxide. Examples of alcohols include divalent alcohols (such as ethylene glycol and propylene glycol) and polyvalent alcohols (such as glycerol and sucrose); examples of phenols include hydroquinone, bisphenol A, etc.
[0079] Examples of polyester polyols include condensation-type polyester polyols prepared by reacting polyvalent alcohols (such as divalent or trivalent alcohols mentioned above) with polybasic acids (such as succinic acid, adipic acid, sebacic acid, maleic acid, dimer acid, trimellitic acid, phthalic acid, terephthalic acid, etc.), polylactone polyols prepared by ring-opening polymerization of lactones (such as ε-caprolactone), their epoxide adducts, and so on.
[0080] The number-average hydroxyl functionality (Fn) of the polyol is preferably 2 or higher (e.g., 2.2-3). Number-average hydroxyl functionality refers to the average number of hydroxyl groups present on the polyol molecule and can be calculated as the ratio of the total number of moles of OH in the polyol to the total number of moles of the polyol.
[0081] The number-average molecular weight of the polyol is preferably 90 to 10,000 g / mol, more preferably 400 to 8,000 g / mol, wherein the number-average molecular weight is determined according to the procedure for determining the number-average molecular weight.
[0082] Therefore, the polyol included in the polyol component is preferably a polyol selected from the group consisting of polyether polyols, polyester polyols and combinations thereof, having a number-average hydroxyl functionality (Fn) of 2 or higher (e.g., 2.2-3), and preferably a number-average molecular weight of 90 to 10,000 g / mol, more preferably 400 to 8,000 g / mol, wherein the number-average molecular weight is determined according to the procedure for determining number-average molecular weight.
[0083] In embodiments of the present invention, the polyol component contains more than 10% by weight of polyol (based on the total weight of the polyol component), preferably more than 20% by weight, more preferably more than 30% by weight, and most preferably more than 40% by weight. In embodiments of the present invention, the polyol component contains less than 80% by weight of polyol (based on the total weight of the polyol component), preferably less than 70% by weight, more preferably less than 60% by weight, and most preferably less than 50% by weight. In preferred embodiments, the amount of polyol contained in the polyol component is in the range of 10% by weight to 80% by weight (based on the total weight of the polyol component), preferably in the range of 20% by weight to 70% by weight, more preferably in the range of 30% by weight to 60% by weight, and most preferably in the range of 40% by weight to 50% by weight.
[0084] In a preferred embodiment of the invention, the polyol component contains a major amount of polyols as described herein, such as greater than 50% by weight (based on the total weight of polyols present in the polyol component), greater than 70% by weight, greater than 85% by weight, greater than 95% by weight, greater than 98% by weight, and preferably greater than 99% by weight. In a highly preferred embodiment of the invention, the polyol component contains a major amount of polyols selected from the group consisting of polyether polyols, polyester polyols, and combinations thereof, such as greater than 50% by weight (based on the total weight of polyols present in the polyol component), greater than 70% by weight, greater than 85% by weight, greater than 95% by weight, greater than 98% by weight, and preferably greater than 99% by weight. In a highly preferred embodiment, the polyol component comprises primarily polyols as described herein, preferably primarily polyols selected from the group consisting of polyether polyols, polyester polyols, and combinations thereof, more preferably primarily polyols selected from the group consisting of polyether polyols, polyester polyols, and combinations thereof, wherein the polyol has a number-average hydroxyl functionality (Fn) of 2 or higher (e.g., 2.2-3), and preferably a number-average molecular weight of 90 to 10,000 g / mol, more preferably 400 to 8,000 g / mol, wherein the number-average molecular weight is determined according to a number-average molecular weight determination procedure.
[0085] The polyol component according to the invention may optionally contain one or more other additives. The total amount of all components in the polyol component is 100% by weight (based on the total weight of the polyol component). In embodiments of the invention, the isocyanate component contains one or more other additives selected from the following: fillers, colorants, rheology modifiers, thickeners, plasticizers, solvents, pH adjusters, crosslinking agents, curing agents, adhesion promoters, dehumidifiers, surfactants, and / or other catalysts.
[0086] According to a preferred embodiment of the invention, the polyol component comprises a filler, preferably selected from mineral fillers, metal oxide fillers, fly ash, bottom ash, carbon black, glass, and combinations thereof. Such fillers can also act as rheology modifiers and / or dehumidifiers. Examples include aluminum silicate, aluminum hydroxide, fumed silica, calcium silicate, magnesium silicate, dolomite, calcium carbonate, barium sulfate, calcium sulfate, glass fiber, hollow glass microspheres, carbon black, chalk, titanium dioxide, zinc oxide, siloxanes, and / or silica. The filler may be surface-modified, and any reference to fillers in this disclosure should be construed as a reference to optionally surface-modified fillers. Surface modification of fillers is well known to those skilled in the art. Preferred surface modifications include surface treatment with fatty acids (e.g., stearic acid) or silanes (e.g., alkoxysilanes). Preferred fillers for the polyol component are fillers comprising silica, calcium carbonate, and / or aluminum silicate, or fillers primarily composed of silica, calcium carbonate, and / or aluminum silicate.
[0087] In embodiments of the present invention, the polyol component contains filler in an amount greater than 10% by weight, preferably greater than 25% by weight, preferably greater than 35% by weight, and preferably greater than 45% by weight (based on the total weight of the polyol component). In embodiments of the present invention, the polyol component contains filler in an amount less than 75% by weight, preferably less than 70% by weight, and preferably less than 65% by weight (based on the total weight of the polyol component). In a preferred embodiment of the present invention, the polyol component contains filler in an amount of 10-75% by weight, more preferably 35-70% by weight, and even more preferably 45-65% by weight (based on the total weight of the polyol component). In a highly preferred embodiment of the present invention, the polyol component contains filler (comprising silica, calcium carbonate, and / or aluminum silicate) in an amount of 10-75% by weight, more preferably 35-70% by weight, and even more preferably 45-65% by weight (based on the total weight of the polyol component).
[0088] In a preferred embodiment of the invention, the polyol component includes a filler such as fumed silica that also acts as a rheology modifier. The rheology modifier is preferably included in the polyol component in an amount of 0.1-10% by weight, more preferably 0.5-8% by weight, more preferably 0.5-4% by weight, and even more preferably 1-3% by weight (based on the total weight of the polyol component).
[0089] In embodiments of the invention, the polyol component contains a curing agent, adhesion promoter, or crosslinking agent. For the purposes of this invention, any compound having two or more isocyanate reactive functional groups and 0 or 1 alcohol functional group is considered a curing agent, adhesion promoter, or crosslinking agent. In the case that the compound is a polymer, this implies an average functionality of isocyanate reactive functional groups that are not alcohols greater than 1.0, preferably greater than 2.0. Examples of suitable curing agents, adhesion promoters, or crosslinking agents include organosilanes (e.g., Coatosil MP200), zirconium ammonium compounds (e.g., Halox XTAIN L-44), compounds having two or more oxazolidinone functional groups, and diamines. Examples of suitable organosilane crosslinking agents, adhesion promoters, or curing agents are silanes according to formula (II) and their hydrolysis or condensation products:
[0090] (R 1 -O) a -Si-(R 2 ) b
[0091] (II)
[0092] in
[0093] a is 3 or 4;
[0094] b is 1 or 0;
[0095] a+b equals 4;
[0096] Where R 1 Each occurrence of is selected from the following groups: hydrogen, C1-C8 alkyl, C1-C8 haloalkyl, C1-C8 aminoalkyl, C2-C8 alkenyl, C3-C8 cycloalkyl, C4-C8 cycloalkenyl, C6-C 10 Aryl, -C(O)R 3 -N=CR 4 R 5 and -N=CR 6 ;
[0097] R 3 R 4 and R 5 Selected from the group consisting of C1-C4 alkyl groups;
[0098] R 6 It is a divalent C2-C8 alkyl group, such that -N=CR 6 It is a cycloalkyl group; and
[0099] R 2 The group is selected from the group consisting of hydrogen and optionally substituted monovalent hydrocarbon groups having 1 to 30 carbon atoms. Preferably, R2 Choose from the group consisting of: hydrogen, C1-C8 alkyl, C2-C8 alkenyl, C1-C8 aminoalkyl, -R 7 NH-R 8 and -R 9 -Z, where R 7 R 8 and R 9 The diamine is selected from the group consisting of C1-C8 alkyl groups, preferably C1-C4 alkyl groups, and wherein Z represents an ethylene oxide group, which is optionally substituted with one or more C1-C4 alkyl groups. Examples of suitable diamines for use as curing agents, adhesion promoters, or crosslinking agents include 1,4-diaminobenzene and 2,4-diaminotoluene. The polyol component preferably contains a curing agent, adhesion promoter, or crosslinking agent selected from compounds of the following: silanes of formula (II) and their hydrolysis or condensation products, diamines, or compounds having two or more oxazolidinone functionalities, preferably selected from compounds having two or more oxazolidinone functionalities. In embodiments of the invention, the polyol component contains a curing agent or crosslinking agent as described herein in an amount of 0.1-10% by weight, preferably 0.25-7.5% by weight, more preferably 0.5-5% by weight, even more preferably 0.75-3.5% by weight, and most preferably 1-2.5% by weight (based on the total weight of the polyol component).
[0100] Any pH adjuster known in the art can be used in the polyol components described herein. Examples of suitable pH adjusters include ammonia, alkylamines, strong acids, and strong bases.
[0101] Any thickener known in the art can be used in the polyol components described herein. Examples of suitable thickeners are polyurethane thickeners (e.g., Rheovis 1190, Tafigel® PUR 40, Tafi®® PUR 55), fumed silica (e.g., Aerosil R974), cellulose derivatives (e.g., Me®cel® 228, ®thocel® Methocel® 311), acrylate thickeners (e.g., Rheovis HS1169, AP1 / 1, Mirox AM), bentonite, hectorite, montmorillonite, and silica® such as Aerosil® 200.
[0102] Any adhesion promoter known in the art can be used in the polyol components described herein. Examples of suitable adhesion promoters are organosilane adhesion promoters selected from the group consisting of aminosilanes, alkoxysilanes, and epoxysilanes, preferably selected from the group consisting of: aminoalkyltrialkoxysilanes, aminoalkylalkyldialkoxysilanes, bis(alkyltrialkoxysilyl)amines, tri(alkyltrialkoxysilyl)amines, tri(alkyltrialkoxysilyl)cyanurates, tri(alkyl-trialkoxy-silyl)isocyanurates, alkoxy-terminated polydimethylsiloxanes containing aminoalkyl side groups (such as ethoxy-terminated (3-aminopropyl)(methyl)polysiloxanes), hydroxyl-terminated polydimethylsiloxanes terminated by N-(3-trimethoxysilyl)propylcyclohexylamine, condensation products of any of the listed silanes, and combinations thereof. Preferably, the alkyl group is C1-C4 alkyl and the alkoxy group is C1-C4 alkoxy.
[0103] Any colorant known in the art can be used in the polyol components described herein. Examples of suitable colorants include titanium dioxide, zinc oxide, iron oxide, antimony oxide, chrome green, chrome yellow, iron blue, siennas, molybdate oranges, and organic pigments (such as para reds, benzidine yellow, toluidine red, lakes, and phthalocyanines), preferably reactive polymers having chromophores.
[0104] Those skilled in the art will understand that a single additive may perform multiple functions; for example, silanes can be used as crosslinking agents and adhesion promoters.
[0105] The polyol component according to the invention is preferably substantially anhydrous. In a preferred embodiment, it contains less than 0.1% by weight of water.
[0106] Preferably, the total combined amount of polyol and filler (preferably mineral filler) in the polyol component is in the range of 85-100% by weight (based on the total weight of the isocyanate component), more preferably in the range of 90-100% by weight, and most preferably in the range of 95-100% by weight.
[0107] The polyol component according to the invention may optionally contain one or more catalysts other than tin catalysts containing sulfur atoms, which may be present in the polyol component and discussed elsewhere herein. Other catalysts present may be any catalyst known in the art and suitable for catalyzing the reaction between the polyol component and the isocyanate component. Examples of suitable catalysts include metal catalysts, amine catalysts, and morpholine catalysts. In some embodiments of the invention, the polyol component contains other metal catalysts, wherein the metal is selected from Sn, Bi, Zn, Ti, Zr, or Al.
[0108] In embodiments of the present invention, the total amount of catalyst present in the polyol component is greater than 0.01% by weight (based on the total weight of the polyol component), preferably greater than 0.05% by weight, more preferably greater than 0.1% by weight, more preferably greater than 0.2% by weight, and more preferably greater than 0.3% by weight. In embodiments of the present invention, the total amount of catalyst present in the polyol component is 0.01-10% by weight (based on the total weight of the polyol component), preferably 0.05-7.5% by weight, and more preferably 0.1-5% by weight. In several embodiments, the total amount of catalyst present in the polyol component is 0.01-10 wt%, 0.01-9.5 wt%, 0.01-9 wt%, 0.01-8.5 wt%, 0.01-8 wt%, 0.01-7.5 wt%, 0.01-7 wt%, 0.01-6.5 wt%, 0.01-6 wt%, 0.01-5.5 wt%, 0.01-5 wt%, 0.01-4.5 wt%, 0.01-4 wt%, 0.01-3.5 wt%, 0.01-3 wt%, 0.01-2.5 wt%, 0.01-2 wt%, 0.01-1.5 wt%, and 0.01-1 wt% (based on the total weight of the polyol component). In several embodiments, the total amount of catalyst present in the polyol component is 0.05-10 wt%, 0.05-9.5 wt%, 0.05-9 wt%, 0.05-8.5 wt%, 0.05-8 wt%, 0.05-7.5 wt%, 0.05-7 wt%, 0.05-6.5 wt%, 0.05-6 wt%, 0.05-5.5 wt%, 0.05-5 wt%, 0.05-4.5 wt%, 0.05-4 wt%, 0.05-3.5 wt%, 0.05-3 wt%, 0.05-2.5 wt%, 0.05-2 wt%, 0.05-1.5 wt%, and 0.05-1 wt% (based on the total weight of the polyol component). In several embodiments, the total amount of catalyst present in the polyol component is 0.1-10 wt%, 0.1-9.5 wt%, 0.1-9 wt%, 0.1-8.5 wt%, 0.1-8 wt%, 0.1-7.5 wt%, 0.1-7 wt%, 0.1-6.5 wt%, 0.1-6 wt%, 0.1-5.5 wt%, 0.1-5 wt%, 0.1-4.5 wt%, 0.1-4 wt%, 0.1-3.5 wt%, 0.1-3 wt%, 0.1-2.5 wt%, 0.1-2 wt%, 0.1-1.5 wt%, and 0.1-1 wt% (based on the total weight of the polyol component).In several embodiments, the total amount of catalyst present in the polyol component is 0.2-10 wt%, 0.2-9.5 wt%, 0.2-9 wt%, 0.2-8.5 wt%, 0.2-8 wt%, 0.2-7.5 wt%, 0.2-7 wt%, 0.2-6.5 wt%, 0.2-6 wt%, 0.2-5.5 wt%, 0.2-5 wt%, 0.2-4.5 wt%, 0.2-4 wt%, 0.2-3.5 wt%, 0.2-3 wt%, 0.2-2.5 wt%, 0.2-2 wt%, 0.2-1.5 wt%, and 0.2-1 wt% (based on the total weight of the polyol component). In several embodiments, the total amount of catalyst present in the polyol component is 0.3-10 wt%, 0.3-9.5 wt%, 0.3-9 wt%, 0.3-8.5 wt%, 0.3-8 wt%, 0.3-7.5 wt%, 0.3-7 wt%, 0.3-6.5 wt%, 0.3-6 wt%, 0.3-5.5 wt%, 0.3-5 wt%, 0.3-4.5 wt%, 0.3-4 wt%, 0.3-3.5 wt%, 0.3-3 wt%, 0.3-2.5 wt%, 0.3-2 wt%, 0.3-1.5 wt%, and 0.3-1 wt% (based on the total weight of the polyol component).
[0109] In a preferred embodiment of the invention, the viscosity of the polyol component is in the range of 0.3 – 2000 Pa·s, wherein the viscosity is determined according to a viscosity measurement procedure, preferably in the range of 0.5 – 1400 Pa·s.
[0110] Tin catalysts containing sulfur atoms
[0111] According to a preferred embodiment of the invention (and according to the first aspect of the invention), the polyol component and / or isocyanate component comprises a tin catalyst, wherein the tin catalyst comprises sulfur atoms. The tin catalyst comprising sulfur atoms can be any tin catalyst comprising sulfur atoms suitable for catalyzing the formation of polyurethane adhesives, such as a tin catalyst comprising a thiol or its salt and / or derivative.
[0112] The tin catalyst present in the polyol component and / or isocyanate component may include a single tin catalyst or multiple tin catalysts.
[0113] In a preferred embodiment of the present invention, the tin catalyst containing sulfur atoms is selected from the group consisting of tin thiolates, tin mercaptoacetates and combinations thereof, and is preferably selected from the group consisting of dialkyltin thiolates, dialkyltin mercaptoacetates and combinations thereof.
[0114] In embodiments of the present invention, the tin catalyst containing sulfur atoms is a compound according to formula (I) or a salt thereof.
[0115]
[0116] (I)
[0117] Where R 1 Selected from -SR 5 and -S(CH2) n COOR 6 And R 2 R 3 and R 4 Each independently selected from -SR 5 -S(CH2) n COOR 6 -R 5 OCOR 6 and -OR 5 , where n is an integer from 1 to 3 (preferably n is 1), and R 5 and R 6 Each is independently selected from -H and C1-C 20 Hydrocarbon groups, preferably selected from -H and C1-C 12 The hydrocarbon group, more preferably selected from -H and C1-C8 hydrocarbon groups, and most preferably selected from -H and C3-C8 hydrocarbon groups. The hydrocarbon group is preferably an alkyl group, with R being the most preferred. 5 and R 6 Each is independently selected from -H and C1-C 20 Alkyl groups, preferably selected from -H and C1-C 12 Alkyl, more preferably selected from -H and C1-C8 alkyl, most preferably selected from -H and C3-C8 alkyl.
[0118] In a preferred embodiment of the present invention, R 1 and R 2 Each independently selected from -SR 5 and -S(CH2) n COOR 6 And R 3 and R 4 Each independently selected from -SR 5 -S(CH2) n COOR 6 -R 5 OCOR 6 and -OR 5 , where n is an integer from 1 to 3 (preferably n is 1), and R 5 and R 6 Each is independently selected from -H and C1-C 20 Hydrocarbon groups, preferably selected from -H and C1-C 12The hydrocarbon group, more preferably selected from -H and C1-C8 hydrocarbon groups, and most preferably selected from -H and C3-C8 hydrocarbon groups. In a more preferred embodiment of the invention, R 1 and R 2 Each independently selected from -SR 5 and -S(CH2) n COOR 6 And R 3 and R 4 Each independently selected from -SR 5 -S(CH2) n COOR 6 and -R 5 , where n is an integer from 1 to 3 (preferably n is 1), and R 5 and R 6 Each is independently selected from -H and C1-C 12 The hydrocarbon group, more preferably selected from -H and C1-C8 hydrocarbon groups, and most preferably selected from -H and C3-C8 hydrocarbon groups. In any of these embodiments, R is preferred. 6 It is -H,R 1 and R 2 Same, and R 3 With R 4 Same as or the same as R 1 and R 2 Same. The hydrocarbon group is preferably an alkyl group.
[0119] In the most preferred embodiment of the invention, R 1 and R 2 Each is independently selected from -S(CH2) n COOR 6 And R 3 With R 4 Each is independently selected from -S(CH2) n COOR 6 and -R 5 , where n is an integer from 1 to 3 (preferably n is 1), and R 5 and R 6 Each is independently selected from -H and C1-C 12 The hydrocarbon group, more preferably selected from -H and C3-C8 hydrocarbon groups. In any of these embodiments, R is preferred. 6 It is -H,R 1 and R 2 Same, and R 3 With R 4 Same as or the same as R 1 and R 2 Same. R 5 Preferred selection from C1-C 12Alkyl, more preferably C1-C8 alkyl, most preferably C3-C8 alkyl, such as butyl and octyl. Octyl is preferably selected from branched octyl isomers.
[0120] In a preferred embodiment of the invention, the tin catalyst containing sulfur atoms is selected from the group consisting of:
[0121] Dioctyltin dilauryl thiolate,
[0122] Dimethyltinbis(2-ethylhexylthioacetate)
[0123] Dioctyltinbis(2-ethylhexylthioacetate)
[0124] Octyltin tri(2-ethylhexyl mercaptoacetate),
[0125] Dibutyltin bis(2-ethylhexyl mercaptoacetate),
[0126] Dimethyltin diisooctyl mercaptoacetate,
[0127] Methyltin triisooctyl mercaptoacetate,
[0128] Dimethyltin dilauryl thiolate,
[0129] Dibutyltin dilauryl thiolate,
[0130] Dioctyltin di(mercaptoacetate)
[0131] Salts thereof and combinations thereof, preferably dioctyltin di(thioglycolate) (CAS 26401-97-8, commercially available from TIBCHEMICALS as TIB KAT® 214), dioctyltin bis(2-ethylhexylthioglycolate) (CAS 15571-58-1, commercially available from FOMREZ as contained in Fomorez® UL-21), octyltin tri(2-ethylhexylthioglycolate) (CAS 27107-89-7, commercially available from FOMREZ as contained in Fomorez® UL-21), and combinations thereof.
[0132] In embodiments of the present invention, the amount of the tin catalyst containing sulfur atoms in the polyol component and / or isocyanate component is greater than 0.01% by weight (based on the total weight of the components), preferably greater than 0.05% by weight, more preferably greater than 0.1% by weight, more preferably greater than 0.2% by weight, and more preferably greater than 0.3% by weight. In embodiments of the present invention, the amount of the tin catalyst containing sulfur atoms in the polyol component and / or isocyanate component is less than 10% by weight (based on the total weight of the components), preferably less than 7.5% by weight, more preferably less than 5% by weight, more preferably less than 2.5% by weight, and more preferably less than 1% by weight. In a preferred embodiment of the present invention, the amount of the tin catalyst containing sulfur atoms in the polyol component and / or isocyanate component is 0.01-10% by weight (based on the total weight of the components), preferably 0.05-7.5% by weight, more preferably 0.1-5% by weight, even more preferably 0.2-2.5% by weight, and most preferably 0.3-1% by weight. In several embodiments, the total amount of sulfur-containing tin catalyst present in the polyol component and / or isocyanate component is 0.01-10 wt%, 0.01-9.5 wt%, 0.01-9 wt%, 0.01-8.5 wt%, 0.01-8 wt%, 0.01-7.5 wt%, 0.01-7 wt%, 0.01-6.5 wt%, 0.01-6 wt%, 0.01-5.5 wt%, 0.01-5 wt%, 0.01-4.5 wt%, 0.01-4 wt%, 0.01-3.5 wt%, 0.01-3 wt%, 0.01-2.5 wt%, 0.01-2 wt%, 0.01-1.5 wt%, and 0.01-1 wt% (based on the total weight of the polyol component and / or isocyanate component). In several embodiments, the total amount of sulfur-containing tin catalyst present in the polyol component and / or isocyanate component is 0.05-10 wt%, 0.05-9.5 wt%, 0.05-9 wt%, 0.05-8.5 wt%, 0.05-8 wt%, 0.05-7.5 wt%, 0.05-7 wt%, 0.05-6.5 wt%, 0.05-6 wt%, 0.05-5.5 wt%, 0.05-5 wt%, 0.05-4.5 wt%, 0.05-4 wt%, 0.05-3.5 wt%, 0.05-3 wt%, 0.05-2.5 wt%, 0.05-2 wt%, 0.05-1.5 wt%, and 0.05-1 wt% (based on the total weight of the polyol component and / or isocyanate component).In several embodiments, the total amount of tin catalyst containing sulfur atoms present in the polyol component and / or isocyanate component is 0.1-10 wt%, 0.1-9.5 wt%, 0.1-9 wt%, 0.1-8.5 wt%, 0.1-8 wt%, 0.1-7.5 wt%, 0.1-7 wt%, 0.1-6.5 wt%, 0.1-6 wt%, 0.1-5.5 wt%, 0.1-5 wt%, 0.1-4.5 wt%, 0.1-4 wt%, 0.1-3.5 wt%, 0.1-3 wt%, 0.1-2.5 wt%, 0.1-2 wt%, 0.1-1.5 wt%, and 0.1-1 wt% (based on the total weight of the polyol component and / or isocyanate component). In several embodiments, the total amount of sulfur-containing tin catalyst present in the polyol component and / or isocyanate component is 0.2-10 wt%, 0.2-9.5 wt%, 0.2-9 wt%, 0.2-8.5 wt%, 0.2-8 wt%, 0.2-7.5 wt%, 0.2-7 wt%, 0.2-6.5 wt%, 0.2-6 wt%, 0.2-5.5 wt%, 0.2-5 wt%, 0.2-4.5 wt%, 0.2-4 wt%, 0.2-3.5 wt%, 0.2-3 wt%, 0.2-2.5 wt%, 0.2-2 wt%, 0.2-1.5 wt%, and 0.2-1 wt% (based on the total weight of the polyol component and / or isocyanate component). In several embodiments, the total amount of sulfur-containing tin catalyst present in the polyol component and / or isocyanate component is 0.3-10 wt%, 0.3-9.5 wt%, 0.3-9 wt%, 0.3-8.5 wt%, 0.3-8 wt%, 0.3-7.5 wt%, 0.3-7 wt%, 0.3-6.5 wt%, 0.3-6 wt%, 0.3-5.5 wt%, 0.3-5 wt%, 0.3-4.5 wt%, 0.3-4 wt%, 0.3-3.5 wt%, 0.3-3 wt%, 0.3-2.5 wt%, 0.3-2 wt%, 0.3-1.5 wt%, and 0.3-1 wt% (based on the total weight of the polyol component and / or isocyanate component).
[0133] In some embodiments of the present invention, the tin catalyst containing sulfur atoms is present in the polyol component but not in the isocyanate component. In some embodiments of the present invention, the tin catalyst containing sulfur atoms is present in the isocyanate component but not in the polyol component. In some embodiments of the present invention, the tin catalyst containing sulfur atoms is present in both the polyol component and the isocyanate component.
[0134] In some preferred embodiments of the present invention, the amount of the tin catalyst containing sulfur atoms in the polyol component is greater than 0.01% by weight (based on the total weight of the polyol component), preferably greater than 0.05% by weight, more preferably greater than 0.1% by weight, more preferably greater than 0.2% by weight, and more preferably greater than 0.3% by weight. In embodiments of the present invention, the amount of the tin catalyst containing sulfur atoms in the polyol component is less than 10% by weight (based on the total weight of the polyol component), preferably less than 7.5% by weight, more preferably less than 5% by weight, more preferably less than 2.5% by weight, and more preferably less than 1% by weight. In a preferred embodiment of the present invention, the amount of the tin catalyst containing sulfur atoms in the polyol component is 0.01-10% by weight (based on the total weight of the polyol component), preferably 0.05-7.5% by weight, more preferably 0.1-5% by weight, even more preferably 0.2-2.5% by weight, and most preferably 0.3-1% by weight. In several embodiments, the amount of the tin catalyst containing sulfur atoms in the polyol component is 0.01-10 wt%, 0.01-9.5 wt%, 0.01-9 wt%, 0.01-8.5 wt%, 0.01-8 wt%, 0.01-7.5 wt%, 0.01-7 wt%, 0.01-6.5 wt%, 0.01-6 wt%, 0.01-5.5 wt%, 0.01-5 wt%, 0.01-4.5 wt%, 0.01-4 wt%, 0.01-3.5 wt%, 0.01-3 wt%, 0.01-2.5 wt%, 0.01-2 wt%, 0.01-1.5 wt%, and 0.01-1 wt% (based on the total weight of the polyol component). In several embodiments, the amount of the tin catalyst containing sulfur atoms in the polyol component is 0.05-10 wt%, 0.05-9.5 wt%, 0.05-9 wt%, 0.05-8.5 wt%, 0.05-8 wt%, 0.05-7.5 wt%, 0.05-7 wt%, 0.05-6.5 wt%, 0.05-6 wt%, 0.05-5.5 wt%, 0.05-5 wt%, 0.05-4.5 wt%, 0.05-4 wt%, 0.05-3.5 wt%, 0.05-3 wt%, 0.05-2.5 wt%, 0.05-2 wt%, 0.05-1.5 wt%, and 0.05-1 wt% (based on the total weight of the polyol component).In several embodiments, the amount of the tin catalyst containing sulfur atoms present in the polyol component is 0.1-10 wt%, 0.1-9.5 wt%, 0.1-9 wt%, 0.1-8.5 wt%, 0.1-8 wt%, 0.1-7.5 wt%, 0.1-7 wt%, 0.1-6.5 wt%, 0.1-6 wt%, 0.1-5.5 wt%, 0.1-5 wt%, 0.1-4.5 wt%, 0.1-4 wt%, 0.1-3.5 wt%, 0.1-3 wt%, 0.1-2.5 wt%, 0.1-2 wt%, 0.1-1.5 wt%, and 0.1-1 wt% (based on the total weight of the polyol component). In several embodiments, the amount of the tin catalyst containing sulfur atoms in the polyol component is 0.2-10 wt%, 0.2-9.5 wt%, 0.2-9 wt%, 0.2-8.5 wt%, 0.2-8 wt%, 0.2-7.5 wt%, 0.2-7 wt%, 0.2-6.5 wt%, 0.2-6 wt%, 0.2-5.5 wt%, 0.2-5 wt%, 0.2-4.5 wt%, 0.2-4 wt%, 0.2-3.5 wt%, 0.2-3 wt%, 0.2-2.5 wt%, 0.2-2 wt%, 0.2-1.5 wt%, and 0.2-1 wt% (based on the total weight of the polyol component). In several embodiments, the amount of the tin catalyst containing sulfur atoms in the polyol component is 0.3-10 wt%, 0.3-9.5 wt%, 0.3-9 wt%, 0.3-8.5 wt%, 0.3-8 wt%, 0.3-7.5 wt%, 0.3-7 wt%, 0.3-6.5 wt%, 0.3-6 wt%, 0.3-5.5 wt%, 0.3-5 wt%, 0.3-4.5 wt%, 0.3-4 wt%, 0.3-3.5 wt%, 0.3-3 wt%, 0.3-2.5 wt%, 0.3-2 wt%, 0.3-1.5 wt%, and 0.3-1 wt% (based on the total weight of the polyol component).
[0135] In embodiments of the invention, the sulfur-containing tin catalyst as described herein is present in the polyol component and / or isocyanate component in an amount providing at least 100 ppm (w / w) tin (by total weight of said components), preferably greater than 250 ppm (w / w), more preferably greater than 500 ppm (w / w) and / or less than 2500 ppm (w / w) tin (by total weight of said components), preferably less than 2000 ppm, more preferably less than 1500 ppm. In embodiments of the invention, the total amount of tin from the sulfur-containing tin catalyst present in the polyol component and / or isocyanate component is at least 100 ppm (w / w) tin (by total weight of said components), preferably greater than 250 ppm (w / w), more preferably greater than 500 ppm (w / w) and / or less than 2500 ppm (w / w) tin (by total weight of said components), preferably less than 2000 ppm, more preferably less than 1500 ppm.
[0136] In embodiments of the invention, the sulfur-containing tin catalyst as described herein is present in the polyol component in an amount providing at least 100 ppm (w / w) tin (by total weight of the polyol component), preferably greater than 250 ppm (w / w), more preferably greater than 500 ppm (w / w) and / or less than 2500 ppm (w / w) tin (by total weight of the polyol component), preferably less than 2000 ppm, more preferably less than 1500 ppm. In embodiments of the invention, the total amount of tin from the sulfur-containing tin catalyst present in the polyol component is at least 100 ppm (w / w) tin (by total weight of the polyol component), preferably greater than 250 ppm (w / w), more preferably greater than 500 ppm (w / w) and / or less than 2500 ppm (w / w) tin (by total weight of the polyol component), preferably less than 2000 ppm, more preferably less than 1500 ppm.
[0137] Other features of the kit
[0138] As shown in the appended examples, the inventors have discovered that the kit according to the invention allows for the realization of various advantageous properties of the resulting component mixture and the cured adhesive.
[0139] Based on the guidelines provided herein for formulating polyol and isocyanate components, the inventors have discovered that it is possible to provide low-viscosity, easily dispensable components that still have a long pot life and can quickly achieve high bond strength. Therefore, in embodiments, kits of the present invention are provided, wherein:
[0140] • The viscosity of the polyol component is in the range of 0.3 – 2000 Pa·s, wherein the viscosity is determined according to the viscosity measurement procedure, preferably in the range of 0.8-1200 Pa·s;
[0141] • The viscosity of the isocyanate component is in the range of 0.3 - 2000 Pa·s, wherein the viscosity is determined according to a viscosity measurement procedure, preferably in the range of 0.8 - 1200 Pa·s; and / or
[0142] • The viscosity of the mixture of polyol component and isocyanate component, measured immediately after mixing, is in the range of 0.3-2000 Pa·s, wherein the viscosity is determined according to a viscosity measurement procedure, preferably in the range of 0.8-1200 Pa·s, and wherein the mixture of polyol component and isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5.
[0143] In a preferred embodiment of the invention, a kit as described herein is provided, wherein µ 30 µ0 is less than 3:1, preferably less than 2:1, and where µ 90 The viscosity of the mixture of polyol and isocyanate components is greater than 10:1, preferably greater than 15:1, where µ0 is the viscosity measured immediately after mixing. The mixture of polyol and isocyanate components is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5. 30 The viscosity is the same mixture measured 30 minutes after mixing, and the µ viscosity is... 90 The viscosity is the same mixture measured 90 minutes after mixing, and these viscosities are determined according to the viscosity measurement procedure.
[0144] In a preferred embodiment of the invention, a kit as described herein is provided, wherein t 2000 Greater than 45 minutes, preferably greater than 50 minutes, more preferably greater than 60 minutes, where t 2000 It is the time required for the viscosity of the mixture of polyol component and isocyanate component to reach 2000 Pa·s (the measurement begins immediately after the two components are mixed), wherein the mixture of polyol component and isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5, and wherein the viscosity is determined according to a viscosity measurement procedure.
[0145] In a preferred embodiment of the invention, a kit as described herein is provided, wherein the lap shear strength of the mixture of the polyol component and the isocyanate component, measured after curing at 23°C for 5 hours, is greater than 0.8 N / mm. 2 Preferably, the strength is higher than 1 N / mm 2 More preferably, higher than 1.5 N / mm 2 The optimal value is higher than 2 N / mm 2 The mixture of the polyol component and the isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5, and the lap shear strength is measured according to the lap shear strength testing procedure described herein. The mixture is preferably prepared with a polyol component:isocyanate component weight ratio in the range of 0.8-1.2, preferably 0.9-1.1, and preferably about 1. In some embodiments, the lap shear strength of the mixture of the polyol component and the isocyanate component, measured after curing at 23°C for 5 hours, is higher than 2.7 N / mm. 2 .
[0146] In several preferred embodiments of the invention, kits as described herein are provided in which the lap shear strength, measured after curing the mixture of the polyol component and the isocyanate component at 5°C for 24 hours, is greater than 1 N / mm. 2 Preferably, the strength is higher than 1.3 N / mm 2 More preferably, it is higher than 1.5 N / mm 2 The optimal value is higher than 2 N / mm 2 The mixture of the polyol component and the isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5, and the lap shear strength is measured according to the lap shear strength testing procedure described herein. The mixture is preferably prepared with a polyol component:isocyanate component weight ratio in the range of 0.8-1.2, preferably 0.9-1.1, and preferably about 1. In some embodiments, the lap shear strength of the mixture of the polyol component and the isocyanate component, measured 5 hours after mixing, is higher than 2.7 N / mm. 2 .
[0147] In a preferred embodiment of the invention, a kit as described herein is provided, wherein the lap shear strength, measured after curing the mixture of the polyol component and the isocyanate component at 23°C for one week, is greater than 0.8 N / mm. 2 Preferably, the ratio is higher than 2 N / mm 2 More preferably, it is higher than 3 N / mm 2 The optimal value is higher than 4 N / mm 2The mixture of the polyol component and the isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5, and the lap shear strength is measured according to the lap shear strength testing procedure described herein. The mixture is preferably prepared with a polyol component:isocyanate component weight ratio in the range of 0.8-1.2, preferably 0.9-1.1, and preferably about 1.
[0148] adhesives
[0149] In another aspect, the present invention provides a polyurethane adhesive that is obtained by mixing a polyol component and an isocyanate component of a kit as described herein, preferably by mixing the components at an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5.
[0150] The adhesive preferably has the lap shear strength, Shore (hardness tester) hardness, tensile strength and / or shrinkage as described herein in the context of the kit.
[0151] Uses and methods related to this invention
[0152] In another aspect, the present invention provides the use of the kits or adhesives described herein for joining two or more objects. The joined objects may be of the same or different materials. In some embodiments, the materials of the objects are selected from metals, plastics (including fiber-reinforced plastics and foamed polymers), wood, bitumen, glass, fiberglass, mineral wool, bitumen roofing materials, plaster, and concrete. In some embodiments, the use is for joining a first object (preferably a foamed polymer, such as expanded polystyrene) as an insulation material to a second object (selected from wood, metal, or polyvinyl chloride). Such applications can be seen, for example, in the production of so-called sandwich insulation panels. A preferred use is for joining an aluminum object to another object, and most preferably for joining two or more aluminum objects.
[0153] In another aspect, the present invention provides a method for forming a polyurethane adhesive, comprising:
[0154] • Provide isocyanate components as described herein;
[0155] • Provide polyol components as described herein; and
[0156] • The isocyanate component and the polyol component are mixed, preferably at an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, more preferably 0.9 to 3.0, and more preferably 1.0 to 2.5.
[0157] Preferably, the mixing is carried out at a volume ratio of polyol component to isocyanate component in the range of 0.8-1.2, preferably in the range of 0.9-1.1, and more preferably about 1.
[0158] In another aspect, the present invention provides a method for joining two or more objects, comprising:
[0159] i. Provide two or more objects to be joined;
[0160] ii. Apply the polyurethane adhesive as described herein to the surface of one or more of the objects to be joined;
[0161] iii. Contact the objects to be joined such that the polyurethane adhesive contacts two or more of the objects to be joined.
[0162] The contact should be made before the polyurethane adhesive has fully cured, for example, within 20 minutes after mixing the polyol and isocyanate components.
[0163] As used herein, the term "bonded" substrates should be interpreted as meaning that the substrates are bonded together by a polyurethane adhesive. Typically, the substrates do not actually contact each other in the area where the adhesive is applied because there is a layer of adhesive between the substrates in the area where the adhesive is applied. In some embodiments, the method may also include applying pressure and / or securing the objects to be bonded during step (iii).
[0164] As those skilled in the art will understand, for two substrates to be bonded, at least two surfaces are always in contact with the polyurethane adhesive at the moment the two substrates are actually bonded. However, in step (ii), the polyurethane adhesive may be applied to only one of the surfaces to be bonded, such that the other surface to be bonded only comes into contact with the polyurethane adhesive at the moment the two substrates are actually bonded in step (iii). Alternatively, the polyurethane adhesive may be applied to both surfaces to be bonded in step (ii) before the moment the two substrates are actually bonded in step (iii). By applying the adhesive independently to the two surfaces before they are bonded, improved adhesion to the substrates can be obtained.
[0165] In another aspect, the present invention provides the use of a tin catalyst containing sulfur atoms, as described herein, for delaying the curing of a mixture of a polyol and an isocyanate component, as described herein. The polyol is preferably a polyol as described herein, and is preferably provided in the form of a polyol component as described herein.
[0166] Example
[0167] analyze Test Procedure
[0168] Viscosity Measurement Procedure:
[0169] • The method of DIN EN ISO 3219 (2021) was applied using the HR-2 Discovery hybrid rheometer (TAInstruments);
[0170] • Apply the method in Annex B of DIN EN ISO 3219 (2021), in which a combination of an upper rotatable 25mm stainless steel plate and a fixed lower Peltier plate is used instead of a conical plate;
[0171] • Use a temperature of 23.0 °C and maintain it throughout the viscosity measurement process;
[0172] • The gap between the plates is 1000 micrometers; and
[0173] • When testing isocyanate components or polyol components, or polymers contained in one of these components, the reported viscosity is the average viscosity obtained over a 600-second time period (measurement intervals of 120 seconds) through a single-point oscillation test (with a fixed strain of 0.1% and a frequency of 1.0 Hz); and
[0174] • The viscosity reported for the mixture of isocyanate and polyol components is a value obtained by a single-point oscillation test (with a fixed strain of 0.1% and a frequency of 1.0 Hz) at a predetermined time after mixing, wherein the viscosity is measured for 4200 seconds after mixing (with a measurement interval of 120 seconds).
[0175] Procedure for testing the shear strength of lap joints:
[0176] • Thoroughly clean both AlMgSi substrates (each substrate measuring 100 mm x 25 mm x 2 mm) with isopropanol to remove any contaminants or impurities from their surfaces;
[0177] • Prepare a mixture of isocyanate and polyol components using a dual asymmetric centrifugal mixer (such as the Haushchild® SpeedMixer) at 2500 rpm for 30 seconds;
[0178] • Immediately after mixing, apply the mixture to one end of the surface of the first substrate (the application area should be 25 mm x 25 mm x 2 mm) to ensure uniform coverage;
[0179] • Contact the second substrate with the adhesive area (without further fixation) and leave these substrates at a predetermined temperature (5°C or 23°C) and 50% relative humidity for a predetermined curing time.
[0180] • The overlap shear strength of cured substrates is evaluated using the Zwick® Shear Strength Analyzer at a test speed of 10 mm / min.
[0181] Number-average molecular weight determination procedure:
[0182] • The number-average molecular weight of polyol and isocyanate-terminated polymers can be determined using gel permeation chromatography (GPC).
[0183] For polyols, the polymer sample is first dissolved in a suitable solvent such as tetrahydrofuran (THF) or dimethylformamide (DMF) at a concentration ranging from approximately 0.1 to 5 mg / mL. The solution is then filtered through a 0.2 µm membrane filter to remove any particulate matter. The prepared sample is then injected into a GPC system equipped with a size-exclusion column calibrated using polyethylene glycol (PEG) or poly(methyl methacrylate) (PMMA) standards of known molecular weight. Detection is performed using a differential refractive index (RI) detector, an evaporative light scattering (ELSD) detector, or a multi-angle light scattering (MALS) detector. The mobile phase (typically THF or DMF) is maintained at a flow rate of approximately 0.5 to 1.0 mL / min, with a column temperature of 30°C to 50°C. The number-average molecular weight of the polyol is then calculated based on the retention time and a calibration curve obtained from the molecular weight standards.
[0184] • For isocyanate-terminated polymers, special precautions are taken to prevent secondary reactions such as hydrolysis or crosslinking. The polymer is first dissolved in an anhydrous solvent such as tetrahydrofuran (THF) or hexafluoroisopropanol (HFIP) at a concentration of approximately 0.5 to 2 mg / mL. To stabilize the reactive isocyanate groups and prevent undesirable side reactions, a derivatization step can be performed, in which the polymer is reacted with an excess of a capping agent such as butylamine or phenyl isocyanate to form a stable urethane or urea derivative. Subsequently, the derivatized sample is analyzed by GPC using polystyrene or poly(methyl methacrylate) (PMMA) calibration standards. The system is equipped with an RI detector, a UV detector (at 254 nm), or a MALS detector. The number-average molecular weight of the isocyanate-terminated polymer is calculated using the elution chromatogram and the corresponding calibration data.
[0185] Isocyanate components
[0186] The isocyanate component was prepared by adding the different components shown in Table 1 into a glass bottle (which was then sealed to prevent product loss). The resulting mixture was homogenized by vigorous hand shaking and allowed to stand at room temperature (RT) for approximately 4 hours. The free monomer content of this isocyanate component was < 0.06% and the free NCO content was 19.83%.
[0187] Table 1: Composition of the stock solution of isocyanate component
[0188]
[0189] Polyol components (without catalyst)
[0190] Catalyst-free polyol components were prepared by adding the different components shown in Table 2 into glass vials (which were then sealed to prevent product loss). The resulting mixture was homogenized by vigorous hand shaking and allowed to stand at room temperature (RT) for approximately 4 hours.
[0191] Table 2: Composition of the polyol component stock solution
[0192]
[0193] Sample preparation procedure
[0194] All tested samples were prepared by mixing the isocyanate component and polyol component (without catalyst) with different catalysts at 2500 rpm for 30 seconds using a dual asymmetric centrifugal mixer (Haushchild® SpeedMixer). These samples were prepared at a 1:1 weight ratio of isocyanate component to (polyol component + catalyst), resulting in an NCO content of less than 2% by weight.
[0195] Overviews of the different catalysts used can be found in Table 3, and overviews of the different samples prepared can be found in Table 4. Comparative examples have been labeled accordingly.
[0196] Table 3: List of tested catalysts and their corresponding metals and metal contents
[0197]
[0198] Table 4: Composition of each sample, including its corresponding total metal content and time required to reach a viscosity of 2000 Pa·s.
[0199] Table 4 (Part 1)
[0200]
[0201] *The catalyst is formulated and used at 10% by weight in DINP (diisononyl phthalate).
[0202] Table 4 (Part 2)
[0203]
[0204] *The catalyst is formulated and used at 10% by weight in DINP (diisononyl phthalate).
[0205] result
[0206] Immediately after mixing, the samples were tested according to the lap shear strength testing procedure, with curing performed at 5°C (strength measured after 24 hours and 1 week) and 23°C (strength measured after 5 hours). The results are shown in the table below. As can be seen, the polyurethane adhesive samples according to the present invention exhibit a significant, rapid, and robust strength increase, while also having a long pot life. The strength increase is particularly improved at lower temperatures.
[0207] Immediately after mixing, the viscosity of the sample was evaluated using a viscometry procedure, with measurements taken every minute. The time required for the viscosity to reach 2000 Pa·s is considered a representative value for the pot life and is shown in the table below. It can be seen that the sample according to the present invention has a long pot life while also exhibiting the aforementioned excellent strength enhancement.
[0208]
[0209]
Claims
1. A kit for forming a two-component polyurethane adhesive, wherein the kit comprises an isocyanate component and a polyol component, The isocyanate component comprises an isocyanate-terminated polymer. The free monomeric isocyanate (FMI) content of the isocyanate component is equal to or less than 1000 ppm. The polyol component comprises polyols, The polyol component and / or the isocyanate component contains a tin catalyst, wherein the tin catalyst contains sulfur atoms, and the total amount of sulfur-containing tin catalyst present in the polyol component and / or the isocyanate component is greater than 0.01 by weight.
2. The kit according to claim 1, wherein the polyol is selected from the group consisting of polyether polyols, polyester polyols, and mixtures thereof.
3. The kit according to any one of the preceding claims, wherein the number-average molecular weight of the polyol is 90 to 10,000 g / mol, preferably 400 to 8,000 g / mol, wherein the number-average molecular weight is determined according to the number-average molecular weight determination procedure described in paragraph [00117] of the PCT English specification.
4. The kit according to any one of the preceding claims, wherein the number-average hydroxyl functionality (Fn) of the polyol is 2 or higher.
5. The kit according to any one of the preceding claims, wherein, based on the total weight of the polyol component, the total amount of polyols present in the polyol component is in the range of 10% to 80% by weight, preferably in the range of 20% to 70% by weight, more preferably in the range of 30% to 60% by weight, and most preferably in the range of 30% to 50% by weight.
6. The kit according to any one of the preceding claims, wherein the isocyanate-terminated polymer is: • Isocyanate-polyol prepolymers obtainable by polymerizing a first isocyanate monomer with a polyol, preferably isocyanate-polyol prepolymers obtainable by polymerizing a polyol selected from the group consisting of polyether polyols, polyester polyols, or mixtures thereof; or • Isocyanate polymers can be obtained by polymerizing a second isocyanate monomer without the presence of polyols.
7. The kit of claim 6, wherein the first isocyanate monomer and / or the second isocyanate monomer comprises hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), and / or methylene diisocyanate (MDI), wherein the first isocyanate monomer and / or the second isocyanate monomer preferably consists of hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), and / or methylene diisocyanate (MDI).
8. The kit according to claim 6 or 7, wherein the NCO content of the isocyanate-polyol prepolymer is at least 5% by weight (based on the total weight of the isocyanate-polyol prepolymer), preferably at least 8% by weight, and wherein the NCO content of the isocyanate-polymer is at least 13% by weight (based on the total weight of the isocyanate-polyol prepolymer), preferably at least 16% by weight, and most preferably at least 20% by weight.
9. The kit according to any one of the preceding claims, wherein the isocyanate-terminated polymer has: • Viscosity in the range of 0.3 – 2000 Pa·s, wherein the viscosity is determined according to the viscosity test procedure described in paragraph [00115] of the PCT English specification, preferably in the range of 0.5 – 1400 Pa·s; and / or • Number-average molecular weight in the range of 250–10,000 g / mol, preferably 500–5000, wherein the number-average molecular weight is determined according to the number-average molecular weight determination procedure described in paragraph [00117] of the PCT English specification.
10. The kit according to any one of the preceding claims, wherein the polyol component and the isocyanate component each further comprise a filler, preferably selected from the group consisting of mineral fillers, metal oxide fillers, fly ash, bottom ash, carbon black, glass, and combinations thereof, more preferably selected from the group consisting of aluminum silicate, calcium silicate, magnesium silicate, calcium carbonate, barium sulfate, calcium sulfate, glass fiber, carbon black, silicon dioxide, and / or combinations thereof.
11. The kit according to any one of the preceding claims, wherein • The viscosity of the polyol component is in the range of 0.3 – 2000 Pa·s, wherein the viscosity is determined according to the viscosity measurement procedure, preferably in the range of 0.8-1200 Pa·s; • The viscosity of the isocyanate component is in the range of 0.3-2000 Pa·s, wherein the viscosity is determined according to the viscosity measurement procedure, preferably in the range of 0.8-1200 Pa·s; and The viscosity of the mixture of the polyol component and the isocyanate component, measured immediately after mixing, is in the range of 0.3-2000 Pa·s, wherein the viscosity is determined according to the viscosity measurement procedure, preferably in the range of 0.8-1200 Pa·s, and wherein the mixture of the polyol component and the isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.
5. • The viscosity measurement procedure is described in paragraph [00115] of the PCT English specification.
12. The kit according to any one of the preceding claims, wherein the tin catalyst is selected from the group consisting of tin thiols, tin mercaptoacetates and combinations thereof, preferably from the group consisting of dialkyltin thiols, dialkyltin mercaptoacetates and combinations thereof.
13. A kit for forming a two-component polyurethane adhesive, wherein the kit comprises an isocyanate component and a polyol component, The isocyanate component comprises an isocyanate-terminated polymer. The free monomeric isocyanate (FMI) content of the isocyanate component is equal to or less than 1000 ppm. The polyol component comprises polyols, The polyol component and / or the isocyanate component comprises a metal catalyst, wherein the total amount of metal catalyst present in the polyol component and / or the isocyanate component is greater than 0.01% by weight. Where µ 30 µ0 is less than 3:1, preferably less than 2:
1. And among them µ 90 µ0 is greater than 10:1, preferably greater than 15:
1. Wherein µ0 is the viscosity of the mixture of the polyol component and the isocyanate component measured immediately after mixing, wherein the mixture of the polyol component and the isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5; wherein µ 30 The viscosity is the same mixture measured 30 minutes after mixing, and the µ viscosity is... 90 The viscosity is the same mixture measured 90 minutes after mixing, and the viscosity is measured according to the viscosity measurement procedure described in paragraph [00115] of the PCT English specification.
14. A kit for forming a two-component polyurethane adhesive, wherein the kit comprises an isocyanate component and a polyol component, wherein the isocyanate component comprises an isocyanate-terminated polymer, wherein the free monomeric isocyanate (FMI) content of the isocyanate component is equal to or less than 1000 ppm, wherein the polyol component comprises a polyol, wherein the polyol component and / or the isocyanate component comprises a metal catalyst, wherein the total amount of metal catalyst present in the polyol component and / or the isocyanate component is greater than 0.01% by weight, wherein t 2000 Greater than 45 minutes, preferably greater than 50 minutes, more preferably greater than 60 minutes, t 2000 The viscosity of the mixture of the polyol component and the isocyanate component, measured immediately after mixing, reaches 2000 Pa·s, wherein the mixture of the polyol component and the isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5, and wherein the viscosity is measured according to the viscosity measurement procedure described in paragraph [00115] of the PCT specification. The lap shear strength of the mixture of the polyol component and the isocyanate component, measured after curing at 5°C for 24 hours, is greater than 1 N / mm. 2 Preferably, the strength is higher than 1.3 N / mm 2 More preferably, higher than 1.5 N / mm 2 The optimal value is higher than 2 N / mm 2 The lap shear strength is measured according to the lap shear strength test procedure described in paragraph [00116] of the PCT English specification.
15. The kit according to any one of the preceding claims, wherein the lap shear strength of the mixture of the polyol component and the isocyanate component, measured after curing at 23°C for 5 hours, is greater than 0.8 N / mm. 2 Preferably, the ratio is higher than 1 N / mm 2 More preferably, higher than 1.5 N / mm 2 The optimal value is higher than 2 N / mm 2 The mixture of the polyol component and the isocyanate component is prepared with an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.5, and the lap shear strength is measured according to the lap shear strength test procedure described in paragraph [00116] of the PCT English specification.
16. A polyurethane adhesive, said polyurethane adhesive being formed by mixing the polyol component and the isocyanate component of the kit according to any one of claims 1-15, preferably by mixing said components at an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, preferably 0.9 to 3.0, more preferably 1.0 to 2.
5.
17. The kit according to any one of claims 1-15 or the adhesive according to claim 16 for joining two or more objects.
18. A method for forming a polyurethane adhesive, the method comprising: • Provide an isocyanate component as defined in any one of claims 1-15; • Provide a polyol component as defined in any one of claims 1-15; as well as • The isocyanate component and the polyol component are mixed, preferably at an NCO / OH stoichiometric ratio in the range of 0.8 to 5.0, more preferably 0.9 to 3.0, and more preferably 1.0 to 2.
5.
19. The method of claim 18, wherein the mixing is carried out at a volume ratio of polyol component to isocyanate component in the range of 0.8-1.2, preferably in the range of 0.9-1.1, and preferably about 1.
20. A method for joining two or more objects, the method comprising: i. Provide two or more objects to be joined; ii. Apply the polyurethane adhesive according to claim 16 to the surface of one or more of the objects to be joined; iii. Bring the objects to be joined into contact such that the polyurethane adhesive contacts two or more of the objects to be joined.
21. Use of a tin catalyst containing sulfur atoms for delaying the curing of a mixture of a polyol and an isocyanate component as described in any one of claims 1-15.